2021
DOI: 10.3389/fgene.2021.589408
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Transcriptomic Analysis of the miRNA–mRNA Interaction Network in Thin Endometrium

Abstract: Although the thin endometrium (TE) has been widely recognized as a critical factor in implantation failure, the contribution of miRNA–mRNA regulatory network to the development of disease etiology remains to be further elucidated. This study performed an integrative analysis of the miRNA–mRNA expression profiles in the thin and adjacent normal endometrium of eight patients with intrauterine adhesion to construct the transcriptomic regulatory networks. A total of 1,093 differentially expressed genes (DEGs) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…We found that LBR, CPR, and IR were lower in patients with thin endometrium, which were consistence with previous studies (4,22,38). The underlying reason might not only be related to high oxygen levels in basal layer of endometrium, but also relevant to abnormal transcriptional changes in thin endometrium (39)(40)(41). For instance, a recent study revealed that differentially expressed genes and microRNAs, which were enriched in angiogenesis, cell growth regulation, and Wnt signaling pathway, were detected in the mid-secretary phase of thin endometrium compared to adjacent normal endometrial cells (41).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that LBR, CPR, and IR were lower in patients with thin endometrium, which were consistence with previous studies (4,22,38). The underlying reason might not only be related to high oxygen levels in basal layer of endometrium, but also relevant to abnormal transcriptional changes in thin endometrium (39)(40)(41). For instance, a recent study revealed that differentially expressed genes and microRNAs, which were enriched in angiogenesis, cell growth regulation, and Wnt signaling pathway, were detected in the mid-secretary phase of thin endometrium compared to adjacent normal endometrial cells (41).…”
Section: Discussionsupporting
confidence: 91%
“…The underlying reason might not only be related to high oxygen levels in basal layer of endometrium, but also relevant to abnormal transcriptional changes in thin endometrium (39)(40)(41). For instance, a recent study revealed that differentially expressed genes and microRNAs, which were enriched in angiogenesis, cell growth regulation, and Wnt signaling pathway, were detected in the mid-secretary phase of thin endometrium compared to adjacent normal endometrial cells (41). Moreover, our results showed that though a thin endometrium had no effect on MR, but had higher chance of early miscarriage.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the genes were enriched in Wnt signaling pathway. The key signaling pathways are closely related to the basic developmental processes and the control of asymmetric cell division ( Zong et al, 2021 ). A previous study found that the Wnt pathway was activated in congenital CCs, but the activation level was lower than that in cholangiocarcinoma ( Chen et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…S4 A and B ). This may contribute to the impairment of angiogenesis and new blood vessel sprouting and ultimately result in insufficient vascularization, which has been reported as a key cause for thin endometrium ( 16 , 17 ). Expression of VCAN and MGP was significantly up-regulated in the stroma of thin endometrium ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%